2019
DOI: 10.1002/anie.201903354
|View full text |Cite
|
Sign up to set email alerts
|

A Redox‐Confused Bismuth(I/III) Triamide with a T‐Shaped Planar Ground State

Abstract: Reaction of at ethered triamine ligand with Bi-(NMe 2 ) 3 gives aBitriamide,for which aBi I electronic structure is shown to be most appropriate.T he T-shaped geometry at bismuth provides the first structural model for edge inversion in bismuthines and the only example of aplanar geometry for pnictogen triamides.A nalogous phosphorus compounds exhibit ad istorted pyramidal geometry because of different BiÀNa nd PÀNb ond polarities.A lthough considerable Bi I character is indicated for the title Bi triamide,i t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 63 publications
2
94
0
Order By: Relevance
“…All three p-orbitals are engaged in EÀN s bonding in the bent case. [8] The LUMO in the bent geometry is EÀN s*i nn ature and appears trans to the central EÀNb ond as expected for the + +III oxidation state of pnictogen amides. Consequently,i nt he planarg eometry,a vacant p-orbital remains availablep erpendicular to the molecular plane at the central element and it is the LUMO in each case.…”
Section: Implications For Reactivitymentioning
confidence: 69%
See 2 more Smart Citations
“…All three p-orbitals are engaged in EÀN s bonding in the bent case. [8] The LUMO in the bent geometry is EÀN s*i nn ature and appears trans to the central EÀNb ond as expected for the + +III oxidation state of pnictogen amides. Consequently,i nt he planarg eometry,a vacant p-orbital remains availablep erpendicular to the molecular plane at the central element and it is the LUMO in each case.…”
Section: Implications For Reactivitymentioning
confidence: 69%
“…[8] Lithiation of the triamide ligand N 3 H 3 ,f ollowed by reaction with one molar equivalent of AsCl 3 gave compound 2 which was isolated as ac rystalline solid in 55 %y ield. [8] Lithiation of the triamide ligand N 3 H 3 ,f ollowed by reaction with one molar equivalent of AsCl 3 gave compound 2 which was isolated as ac rystalline solid in 55 %y ield.…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…reported on a very interesting bismuth T‐shaped triamide with a planar ground state. This compound exhibited a redox‐confused bismuth(I/III) situation and may thus serve as Bi I ‐donor for a W(CO) 5 fragment, but also as a Bi III source . Recently, Cornella et al.…”
Section: Figurementioning
confidence: 99%
“…This compound exhibited ar edox-confused bismuth(I/III) situation andm ay thus serve as Bi I -donor foraW(CO) 5 fragment, but also as aB i III source. [12] Recently,C ornella et al showedt hat the N,C,N-chelated bismuth(I) compound (Figure1A) wasa ble to serve as a catalystf or the transfer hydrogenation of azo compounds and suggested that the catalytic cycle involves the Bi I ÀBi III redox couple. [13] We have used similarh eavy pnictogen(I) compounds as ligands for transition metals [14] including those in which the antimony atom bridges two Pd atoms [15] ( Figure 1B).…”
mentioning
confidence: 99%